2021
DOI: 10.1002/cam4.3738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prognostic value of different preoperative complete blood count cell ratios in patients with oral cavity cancer treated with surgery and postoperative radiotherapy

Abstract: Background We sought to compare the prognostic significance of different preoperative complete blood count cell ratios in patients with oral cavity squamous cell carcinoma (OSCC) treated with surgery and postoperative radiotherapy (PORT). Methods We retrospectively reviewed the clinical records of 890 patients with OSCC who were treated with surgery and PORT. The following preoperative complete blood count cell ratios were collected: neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A recent study, conducted among patients who had undergone surgical resection, found that pre-operative NLR is an independent predictor of prognosis and could be used as an auxiliary parameter for overall survival (OS) and disease-free survival (DFS) before curative surgery is conducted [ 10 ]. Other studies conducted among patients with OSCC, further supported the role of pre-operative NLR, PLR and LMR as robust predictors for OS and DFS [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A recent study, conducted among patients who had undergone surgical resection, found that pre-operative NLR is an independent predictor of prognosis and could be used as an auxiliary parameter for overall survival (OS) and disease-free survival (DFS) before curative surgery is conducted [ 10 ]. Other studies conducted among patients with OSCC, further supported the role of pre-operative NLR, PLR and LMR as robust predictors for OS and DFS [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 74%
“…In addition, there is a lack of information with regard to post-treatment inflammatory markers and their role in predicting the prognosis of cancer patients. Furthermore, most of these studies have reported on the more well-known markers, such as PLR and NLR [ 8 , 9 , 10 , 11 ]. There are scarce data on the prognostic abilities of other systemic inflammatory markers scoring systems, such as the lymphocyte–to–white blood cell ratio (LWR), the white blood cell–to–haemoglobin ratio (WHR), the derived neutrophil–to–lymphocyte ratio (dNLR) and the systemic immune-inflammation index (SII).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to determine the prognostic importance of survivin in relation to WBC counts, NLR, LMR and PLR, the study group patients (Group 1) were subdivided into 2 sub-groups, such as a Group with high and a Group with low values of each hematologic marker on the basis of cut-off values selected from published data on cancer patients and were compared with the survivin levels. The cut-off values of the parameters were WBC = ≥7.9 × 10 9 /L and <7.9 × 10 9 /L, ANC = ≥4.9 × 10 9 /L and <4.9 × 10 9 /L, ALC = >1.980 × 10 9 /L and ≤1.980 × 10 9 /L, AMC = ≥0.50 × 10 9 /L and <0.50 × 10 9 /L, NLR = ≥2.39 and <2.39, LMR = >3.22 and ≤3.22, PLR = >110.6 and ≤110.6 [56][57][58]. BIRC5 gene sequence analysis data were tabulated in a Microsoft Excel sheet, and the data were presented under the headings: (a) single nucleotide variation, (b) number of subjects, (c) frequency of occurrence of variation in each group (expressed as a percentage (%)), and (d) average concentration of tissue survivin in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, platelet injection further promotes the formation of metastatic nodules in murine cancer metastasis models, suggesting that platelets play a crucial role in cancer cell invasion and metastasis ( Haemmerle et al ., 2017 ; Ichikawa et al ., 2020 ). In line with these data, meta-analyses have revealed that higher platelet-to-lymphocyte ratios and/or platelet counts are significantly correlated with poorer overall survival (OS) in patients with HNSCC and OSCC ( Rachidi et al ., 2014 ; Bardash et al ., 2019 ; Lee et al ., 2020b ; Wu et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%